Beneficial and Detrimental Roles of NLRs in Carcinogenesis - Janowski, Ann M.; Kolb, Ryan; Zhang, Weizhou; Sutterwala, Fayyaz S. (Frontiers in Immunology, 2013)
Inflammation plays a critical role in tumorigenesis and can contribute to oncogenic mutations, tumor promotion, and angiogenesis. Tumor promoting inflammation is driven by many factors including the presence of the pro-inflammatory cytokines interleukin (IL)-1β and IL-18. One major source of IL-1β and IL-18 secretion is through the activation of inflammasomes. Inflammasomes are multiprotein complexes that upon activation lead to the processing and secretion of IL-1β and IL-18 mediated by the cysteine protease caspase-1. Several inflammasomes, including NLRP3, NLRC4, and NLRP6, have been implicated in tumorigenesis. However, inflammasomes play divergent roles in different types of cancer reflecting the complexity of inflammation during tumorigenesis. Understanding the role of inflammasome activation during specific stages of tumorigenesis and also during cancer immunotherapy will help identify novel therapeutic targets that could improve treatment strategies for cancer patients. Here we will discuss recent advances in understanding the mechanism by which NLRs regulate carcinogenesis.